2020
DOI: 10.1002/jhbp.744
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting technical success of endoscopic transpapillary gallbladder drainage for acute cholecystitis

Abstract: Background/PurposeEndoscopic transpapillary gallbladder drainage (ETGBD), including endoscopic nasogallbladder drainage (ENGBD) and endoscopic gallbladder stenting (EGBS), has been reported to be an effective treatment for acute cholecystitis. However, ETGBD is considered to be more difficult than percutaneous transhepatic gallbladder drainage (PTGBD), and few studies have evaluated the factors that affect technical success of the procedure. We investigated the factors predicting its technical success from amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 28 publications
4
45
0
4
Order By: Relevance
“…According to previous reports, the most common cystic duct directions and locations are the proximal, right, and cranial branches [ 15 ]. Maruta et al reported that the cystic duct showed proximal, right, and cranial branches in 76%, 86%, and 80% of the cases, respectively, which is similar to our results [ 16 ]. However, no previous reports have described the diagnostic imaging ability of cystic duct anatomy in patients with acute cholecystitis before performing ETGBD.…”
Section: Discussionsupporting
confidence: 92%
“…According to previous reports, the most common cystic duct directions and locations are the proximal, right, and cranial branches [ 15 ]. Maruta et al reported that the cystic duct showed proximal, right, and cranial branches in 76%, 86%, and 80% of the cases, respectively, which is similar to our results [ 16 ]. However, no previous reports have described the diagnostic imaging ability of cystic duct anatomy in patients with acute cholecystitis before performing ETGBD.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of procedural skills, several considerations are needed. First, according to a recent study, 9 the presence of cystic duct stones, dilation of the common bile duct, and the direction of the cystic duct (proximal and caudal branches) are regarded as important predictors of ETGBD difficulties. Therefore, preoperative magnetic resonance cholangiopancreatography or computed tomography is recommended to observe the location and direction of the confluence of the cystic duct and common bile duct, which is conducive to superselection of the cystic duct.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic transpapillary gallbladder drainage has been reported to be effective, but the success rate varies from 50% to 100% because of difficulties in establishing a passage through ducts [10][11][12][13]. Of the 30 cholecystitis procedures, 12 were completed with the original GW and the original manipulator.…”
Section: Discussionmentioning
confidence: 99%